Beyond sprawl? Regulating growth in Southern Ontario: spotlight on Brampton. - Keil, Roger; Üçoğlu, Murat (Taylor & Francis, 2021)
Over the past two decades, the province of Ontario has deliberately upscaled regional governance by creating a firm framework of land use planning. This entailed plans at the super-regional level that protect a large Greenbelt, designate growth centres, and roll out massive transit investment. This laid the foundation for a “real existing regionalism” in which growth management was produced through multiple conversations, contestations, technological change and territorial restructuring. By all accounts, this regime did not produce a perfect safeguard against sprawl – ostensibly the reason for its existence – but it shifted the practices of regional actors in land use and transportation politics and changed the politics around densities. This regime, which was in place for roughly fifteen years and coterminous with the reign of the Liberal Party of Ontario, has now come to an end. A new provincial government under Doug Ford and the Progressive Conservative Party has begun to redraw regional boundaries, to change the discourse around planning and growth management, and to remake transportation policy. This paper will provide a brief history and assessment of the shifts in recent Ontario sprawl-management regimes and will attempt an early analysis of the consequences for regional governance in the Greater Golden Horseshoe region of Ontario. In order to highlight the cutting-edge dynamics and consequences of these variegated regional governance regimes, we will have a focus on the suburban municipality of Brampton in the Greater Toronto Area. Brampton has a particular socio-economic composition that has the ability to reflect the ongoing political processes and socio-economic relations pertaining to the transformation of land usage over the course of suburban development in the Greater Toronto Area. We will focus on the regional aspect of this peripheral expansion, its governance as well as its link to the housing market dynamics.
Keywords: Zersiedelung; Sprawl; Flächennutzungsplanung; Regionalplanung; Regional Governance